Antarctic Tourism: Nature and Science in the limits of Contemporary Tourism - Pardo Abad, Carlos J.; Nieto Codina, Aurelio (Anales de Geografía de la Universidad Complutense, 2015)
For half a century Antarctic tourism has turned from being an elitist activity to become an economic sector that attracts a growing number of travelers. At present, the current human presence on the Antarctic continent brings about a dichotomy; on the one hand, nature tourists cruises, which may or may not land in Antarctica; on the other hand, scientific missions (another example of tourists), that in many cases maintain a continuous presence throughout the year. These two groups are related in the sense that both inflect undoubted pressure on the environment that international law seeks to regulate. In this paper, we describe both in their geographical contexts and show how they have evolved over the past decades. Desde hace medio siglo el turismo antártico ha pasado de ser una actividad elitista a un sector económico que moviliza a un número creciente de viajeros. En la actualidad, la presencia humana en el continente antártico se caracteriza por su dicotomía; por un lado, los turistas de naturaleza y de crucero, que pueden o no tomar tierra al llegar a la Antártida; por otro, los turistas científicos que son los únicos que en algunos casos pueden mantener una presencia continuada durante todo el año. Estas dos opciones de turismo se relacionan y mantienen una presión sobre el medio ambiente que la legislación internacional trata de regular. En este trabajo, definimos a ambas dentro de su contexto geográfico y presentamos cómo han evolucionado en las últimas décadas. Depuis un demi-siècle le tourisme antarctique a changé d´être une activité elitiste à un secteur économique avec un nombre croissant de voyageurs. Aujourd´hui, la présence humaine sur le continent se caracterise par une dichotomie: d´une parte, les touristes de la nature et de croisière, ce qui peut o une peut pas aller à terre pour atteindre l´Antarctique; d´une autre part, les touristes scientifiques, qui sont les seuls que peuvent avoir une présence continue tout au long de l´année. Ces deux options de tourisme sont en relation et ...